The writings of Jonathan Swift : authoritative texts, backgrounds, criticism - Greenberg, Robert A.;Piper, William Bowman (New York : Norton & Company, 1973)
The purpose of this volume is to make as accessible as possible to the modern reader the best and most characteristic writings of Jonathan Swift.-Pref. This volume contains the complete and definitive texts of virtually all of Swift's major works, as well as a generous selection of his poetry and other writings. Included are Gulliver's Travels, A Tale of a Tub, The Battel of the Books, A Discourse Concerning the Mechanical Operation of the Spirit, numerous essays and other prose pieces, and poems ... A wide range of background materials is presented, including correspondence between Swift and members of his circle and observations by his contemporaries. The critical essays offer evaluations by Norman O. Brown, Samuel Holt Monk, Allan Bloom, Nigel Dennis, Edward W. Rosenheim, Jr., A.E. Dyson, William Frost, C.J. Rawson, Kathleen Williams, Martin Price, Rober M. Adams, and Jay Arnold Levin.-Back cover.
The Text of Gulliver's Travels (1976) -- The Texts if A Tale of a Tub and Other Prose -- The Texts of the Poems -- Backgrounds -- Criticism -- Bibliography.
Includes bibliographical references.
Keywords: SWIFT, JONATHAN -- 1667-1745 -- CRITICISM AND INTERPRETATION